Legal Presumptions and Their Role in Criminal Evidence (A Comparative Study) - Dr. Abdul Hadi Rahman Mohammed Mahmoud (American Journal Of Social Sciences And Humanity Research, 2025)
This study aims to demonstrate the effectiveness of presumptions and their role in criminal evidence by examining their impact on criminal cases as one of the forms of evidence and the extent to which the criminal judge has the freedom to accept them as indirect evidence. Given that the rules of evidence are of paramount importance in all branches of law, and a right without supporting evidence is null and void, evidence is what supports the right and makes it prevail. Presumptions enjoy this importance as a means of proof stipulated by the legislature and adopted by the judiciary and jurisprudence. Presumptions play an important, vital, and effective role in the field of criminal evidence, as original, complementary, or reinforcing evidence, no less important than other forms of evidence. This is especially true given that they have become the most widely used method in criminal justice in our current era, given scientific and technological progress in all fields, especially after criminals resorted to the use of the most accurate modern scientific methods to commit their crimes without leaving traces of their perpetrators. Judicial presumption also plays an important and influential role in determining the credibility of other evidence obtained and existing alongside it in a criminal case. Evidence derived through judicial presumption is similar to a check on other evidence, such as witness testimony, defendants' confessions, and other evidence. Since deducing the unknown fact sought to be proven from a concrete fact is consistent with the remaining circumstances and conditions of the case, deriving a presumption requires the judge to derive the presumption from a fact, then provide evidence for it. He then demonstrates the logical causal relationship between the known fact and the other fact sought to be proven. The oversight imposed by the Court of Cassation on the judge's authority to derive or prove judicial presumption is nothing more than legal oversight of rulings and procedures, about their rationale, whether they occurred in error, whether the judge deviated from his discretionary authority in issuing the final judgment in the case before him, or whether his decision was not consistent with reason and sound logic. Therefore, we find it an essential and unavoidable duty to address the subject of presumption, as it is a very important form of evidence, given the development of the criminal's mind and his attempts to escape punishment. Therefore, we have embarked on writing this research to demonstrate the role of presumptions, whether legal or judicial, and their role in criminal evidence, according to a research plan consisting of two sections. In the first section, we will address the concept of presumptions according to two requirements. In the first, we will explain the definition of presumptions, and in the second, the elements of presumptions. The second section is devoted to the types of presumptions, and in the two requirements, we will discuss legal presumptions in the first section and judicial presumptions in the second section. We will address this in turn according to the established plan, as follows.